The Future of Mobility Scenarios for the United States in 2030 - Zmud, Johanna (RAND Corporation, 2013)
Mobility is defined as the ability to travel from one location to another, regardless of mode or purpose. This report presents two divergent and thought-provoking scenarios for future mobility in the United States in 2030. These were developed using a unique six-step scenario development process. The report also provides suggestions for how transportation planners and policymakers can use these scenarios to inform their own planning.